Inhibition of foam cell formation using a soluble CD68-Fc fusion protein - Daub, Karin; Siegel-Axel, Dorothea; Schönberger, Tanja; Leder, Christoph; Seizer, Peter; Müller, Karin; Schaller, Martin; Penz, Sandra; Menzel, Dagmar; Büchele, Berthold; Bültmann, Andreas; Münch, Götz; et al. (Journal of molecular medicine (Berlin, Germany), 2010)
The appearance of lipid-rich foam cells is a major feature of vulnerable atherosclerotic plaque formation. The transformation of macrophages into foam cells results from excessive uptake of cholesterol-rich particles by scavenger receptors such as CD68. We cloned a CD68-Fc immunoadhesin, a fusion protein consisting of the extracellular domain of the human CD68 and a human Fc domain, and investigated the function in vitro. Specific binding of CD68-Fc to OxLDL with an affinity of 10 nmol/L was determined by surface plasmon resonance and increased binding to lipid-rich human and ApoE −/− mice plaque tissue. This was confirmed both by immunohistochemical staining of CD68-Fc-treated paraffin sections from human plaques and by ELISA-based quantification of CD68-Fc binding to human atherosclerotic plaque extracts. In an in vitro model of macrophage/foam cell formation, CD68-Fc reduced foam cell formation significantly. This was caused both by interference of CD68-Fc with OxLDL uptake into macrophages and platelets and by the inhibition of platelet/OxLDL phagocytosis. Finally, expression of metalloproteinases by macrophages/foam cells was inhibited by CD68-Fc. In conclusion, CD68-Fc seems to be a promising new tool for preventing macrophage/foam cell formation. Thus, CD68-Fc might offer a novel therapeutic strategy for patients with acute coronary syndrome by modulating the generation of vulnerable plaques.